The Contribution of Pre-translation Reading to the Translation Process - Bayrak, Murat (Sakarya Uygulamalı Bilimler Üniversitesi, 2025)
Pre-translation analysis phase is of great significance for the effective carrying out of a translation process. One of the most important stages of pre-translation analysis is pre-translation reading. At this stage, the translator encounters the source text for the first time and identifies possible difficulties that they may arise during translation. The role of pre-translation reading in the translation process is critical yet under-researched. This study aims to reveal the contributions that pre-translation reading can provide to the translator during the translation process. In this direction, a scale that can be used by translators during the pre-translation reading stage has been presented. The questions prepared in this scale have been grouped under the headings of topic - theme, purpose - target audience, text type - genre, and lexis - terminology. A hybrid text containing explanatory, informative and persuasive features has been analysed using the scale. This study has shown that pre-translation reading will greatly facilitate the translator's work during the translation process.

Çeviri sürecinin etkili bir şekilde yürütülebilmesi için çeviri öncesi analiz süreci büyük önem taşımaktadır. Çeviri öncesi analizin en önemli aşamalarından birisi de çeviri öncesi okumadır. Bu aşamada çevirmen kaynak metinle ilk kez karşılaşır ve çeviri sırasında karşılaşabileceği muhtemel zorlukları tespit eder. Çeviri sürecinde çeviri öncesi okuma büyük öneme sahip olmasına rağmen yeterince araştırılmamıştır. Bu çalışma çeviri öncesi okumanın çeviri sürecinde çevirmene sağlayabileceği katkıları ortaya koymayı amaçlamaktadır. Bu doğrultuda çeviri öncesi okuma aşamasında çevirmenler tarafından kullanılabilecek bir ölçek de ortaya konulmuştur. Bu ölçekte hazırlanan sorular konu – tema, amaç – hedef kitle, metin türü – metin alt türü ve söz varlığı – terimler dizgesi başlıkları altında gruplandırılmıştır. Açıklayıcı, bilgilendirici ve ikna edici özellikleri ihtiva eden hibrit bir metin hazırlanan ölçek kullanılarak analiz edilmiştir. Bu çalışmayla çeviri öncesi yapılacak okumanın çeviri sürecinde çevirmenin işini büyük ölçüde kolaylaştıracağı ortaya konulmuştur.
Çeviri Öncesi Okumanın Çeviri Sürecine Katkısı
Keywords: Language Studies (Other); Dil Çalışmaları (Diğer)